El carácter integral, complejo y abierto del sistema colombiano de control de constitucionalidad - Zuluaga Gil, Ricardo (2023)
At the moment, constitutional control in Colombia is based on the study of the effects of the sentences passed by the Constitutional court, and from time to time it is forgotten that the Colombian system is an open, complete and complex one that reaches beyond the pronouncements of this high court. The purpose of this essay is to draw attention to this, taking into account numerous legal, political and administrative cases which seek to ensure the supremacy of the Constitution together with the various procedures set up to ensure compliance with this task.